DIGITAL TRANSFORMATION OF THE LABOR MARKET (Revista Inclusiones, 2020)
Today, the digital transformation of the world economy has become an objective reality. The steady growth in the availability and, as a result, the prevalence of high-speed Internet, the increasing level of autonomy of production and logistics, and the development of digital infrastructure lead to a complex transformation of both markets and industries in general and consumer groups, manufacturers, and retailers in particular. The result of these processes is a radical transformation of the complex of demanded knowledge, skills, and abilities. However, the labor market is formed under the influence of both economic and social processes, which significantly increases its complexity as an object of analysis. The multidimensional impact of digital transformation on the labor market is ambiguous, and the potential synergistic effect of the impact of particular manifestations of digital transformation processes can be both positive and negative. The consequences of such a transformation can be revolutionary. Thus, the problem of effective assessment of the consequences of labor market transformation under the influence of digitalization is extremely relevant. The purpose of this work is to formalize the mathematical vectors of influence of digitalization factors on the development of the labor market. To achieve this goal, digitalization is presented in the form of quantified factors expressed using specific indicators, and the unemployment rate is used as an indicator of the labor market. The main research tool is the regression analysis. As a result, a regression model is obtained that expresses the dualistic nature of the impact of digitalization on the development of the labor market.